The Relationship Between Job Satisfaction and Performance of Inpatient Nurses at Malahayati Islamic Hospital Medan - Nasution, Vidya Syifarani; Wasiyem, Wasiyem; Hasibuan, Rapotan (Newinera Publisher, 2024)
Nurse performance can significantly impact the quality of healthcare services in hospitals, meaning that low nurse performance can affect patient trust, satisfaction, and ultimately, the quality of life and well-being of the community. One factor influencing nurse performance in hospitals is job satisfaction. Job satisfaction reflects employees' feelings towards their jobs. Thus, this study aims to describe the relationship between job satisfaction and nurse performance. The research uses a cross-sectional study design with a sample size of 77 inpatient nurses at Malahayati Islamic Hospital in Medan, employing total sampling techniques. The research instruments include the Job Satisfaction Survey developed by Spector (1994) and the Individual Work Performance Questionnaire (IWPQ) developed by Koopmans et al. (2014). Data analysis was conducted using univariate and bivariate analysis with the chi-square test. The results showed that the majority of nurses' job satisfaction fell into the optimal category (71.4%) and the majority of nurse performance was categorized as good (63.6%). There is a significant relationship between job satisfaction and the performance of inpatient nurses at Malahayati Islamic Hospital in Medan, with a p-value of 0.000 (P value <0.05).